Evaluating time domain reflectometry and coaxial impedance sensors for soil observations by the U.S. Climate Reference Network. Issue 1 (20th February 2020) - Wilson, Timothy B.; Diamond, Howard J.; Kochendorfer, John; Meyers, Tilden P.; Hall, Mark; Casey, Nancy W.; Baker, C. Bruce; Leeper, Ronald; Palecki, Michael A.
Abstract: The objective of this study was to evaluate the performance of two commercial‐grade electromagnetic sensors in measuring soil water content for the U.S. Climate Reference Network (USCRN). One sensor was a 50‐MHz coaxial impedance dielectric sensor (model HydraProbe, Stevens Water Monitoring Systems). The second sensor was a 1‐GHz time domain reflectometry (TDR) sensor (model TDR‐315L, Acclima). There was no substantial difference between both probes in daily mean volumetric soil water content and soil temperature measurements at a 0.1‐m depth in a customized uniform loamy soil testbed in Oak Ridge, TN, from 2016 to 2018, and at select USCRN stations with a variety of soils. However, the TDR‐315L provided more representative soil water content measurements for stations with high‐clay‐content soils than the HydraProbe. These results confirm the necessity of using site‐specific soil properties for soil sensors like the HydraProbe for estimating soil water content in different soil environments. They also suggest that TDR sensors may provide an opportunity to improve USCRN soil moisture measurements in higher‐clay‐content soils. Core Ideas: This study evaluated two electromagnetic sensors. The 50‐MHz HydraProbe was compared with the Acclima 1‐GHz TDR‐315L. Both sensors showed similar soil water content and temperature in a soil testbed. Measurements in clay soils were improved with Acclima TDR‐315Ls over HydraProbes.